Omicron COVID-19 variant outcomes and vaccination in non-severe and non-critical patients at admission - Zhao, Hong; Ye, Wenyi; Yu, Xia; Shi, Yu; Sheng, Jifang (Frontiers in Public Health, 2023)
The clinical data of patients infected with the Omicron variant virus in Zhejiang Province from January to May 14, 2022 were collected retrospectively. We analyzed the differences in symptoms, clinical categories of COVID-19, length of hospital stay, and time for clearance of Omicron variant viral RNA in sputum among the groups receiving a different number of vaccine doses. The analysis showed that as the number of vaccine doses was increased, the frequency of clinical symptoms, such as fever and fatigue, were decreased and the frequency of moderate patients gradually decreased. At the same time, the length of hospital stay was significantly shortened. Based on multivariate analysis, one vaccine dose [odds ratio (OR): 0.21, 95% confidence interval (CI): 0.08−0.56, p = 0.002], two vaccine doses (OR: 0.54, 95% CI: 0.33−0.88, p = 0.013), and three vaccine doses (OR: 0.40, 95% CI: 0.24−-0.64, p < 0.001) shortened the length of hospitalization compared with no vaccination. Persistent virus in the sputum was significantly shortened with one vaccine dose (OR: 0.36, 95% CI: 0.15−0.89, p = 0.027), two vaccine doses (OR: 0.46, 95% CI: 0.27−0.78, p = 0.004), and three vaccine doses (OR: 0.38, 95% CI: 0.22−0.64, p < 0.001) compared with no vaccination. Therefore, we concluded that vaccination was the most effective way to protect people against infection with the Omicron variant. Three vaccine doses provided the greatest protection against the Omicron variant.